Who Eats Well? Sociodemographic and Geographic Predictors of Diet Quality Across 70 Countries Using the Global Diet Recommendation Score and Healthy Eating Index - Chioma Arum; Kristi M. Crowe-White; Nayoung Kim; Seung Eun Jung (Journal of Nutrition Education and Behavior, 2026)

From Revision to Practice: Key Changes in the Revised 2025 Scope and Standards of Practice for Registered Dietitian Nutritionists in Nutrition in Integrative and Functional Medicine - Kristi M. Crowe-White; Monique Richard; Sudha Raj; Carol J. Gilmore; Dana Buelsing Sowards (Journal of the Academy of Nutrition and Dietetics, 2026)

Perceptual grouping can affect the online control of goal-directed hand movements - Emily M. Crowe; Danai T. Vorgia; Liz R. van Hout; Jeroen B. J. Smeets; Eli Brenner (Experimental Brain Research, 2026)
If the target of a goal-directed arm movement is suddenly displaced, the movement is quickly adjusted accordingly. There are situations in which grouping gives the impression that many items have been displaced, although the change that determines the direction of the perceived displacement occurs far from the target. When a single item disappears from one end of a row of items just when an item appears at the other end, it looks as if a single item is displaced from one end to the other (element motion). But if the whole row of items briefly disappears when this change occurs, the whole row seems to have been displaced (group motion). We asked participants to move their finger to a purple target item at the centre of a row of equally spaced black items. Hand movements towards the target were adjusted in the direction of both element and group motion. The adjustment of the movement was especially clear for short rows of items. Importantly, the response was much more vigorous under conditions that give rise to group motion than under conditions that give rise to element motion. Thus, a displacement that is propagated to the target through grouping can affect goal-directed movements.

The extent of oil palm cultivation in Key Biodiversity Areas - Fraser Bell; Graeme M. Buchanan; Olivia Crowe; Alison E. Beresford (Biodiversity and Conservation, 2026)

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Sedimentary Mo isotope variability reflects climate-driven water column oxygenation changes in ferruginous Lake Towuti, Indonesia over the last ∼30 ka BP - Adrianus Damanik; Martin Wille; Qasid Ahmad; Sean A. Crowe; Kohen W. Bauer; Martin Grosjean; Sri Yudawati Cahyarini; Satria Bijaksana; James M. Russell; Hendrik Vogel (Quaternary Science Reviews, 2025)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Effectiveness of Key Biodiversity Areas in representing global avian diversity - Tom P. Lansley; Olivia Crowe; Stuart H. M. Butchart; David P. Edwards; Gavin H. Thomas (Conservation Biology, 2025)
Key Biodiversity Areas (KBAs) are the largest and most complete network of significant sites for the global persistence of biodiversity. Although important sites for birds worldwide have been relatively well assessed, a key question is how effectively the global KBA network represents avian diversity. We identified bird species, orders, habitats, and geographic regions that are underrepresented by KBAs. Area of Habitat (AOH) maps for 10,517 terrestrial bird species were cropped and masked by the extent of each KBA. Almost all species had at least one part of their seasonal distribution in one or more KBAs. Twenty‐nine species had no habitat overlap with KBAs, and 1900 species had 2 ). Terrestrial bird species of tropical forests were 12.8% better represented in KBAs than expected by chance, whereas boreal and temperate forest species were less well represented than expected by chance (74.4% and 25.1%, respectively). Among avian orders, Anseriformes and Charadriiformes were underrepresented in KBAs (29.0% and 17.9%, respectively), whereas Trogoniformes and Psittaciformes were better represented (16.2% and 6.9%, respectively) than expected by chance. Bird species for potential KBA identification include marsh antwren ( Formicivora paludicola ) and Tabar pitta ( Erythropitta splendida ). These are mainly due to recent changes in species’ taxonomy or their International Union for Conservation of Nature Red List category. Identifying poorly represented species and where they occur highlights shortfalls where expansion of the network could bring conservation benefits.

Clinical Implication of Anthropometric Indices Compared to the Gold Standard Air Displacement Plethysmography (BODPOD) for Body Composition Assessment in a Racially Diverse Sample - S. Sarihi; D. Mensah; M. Qiao; J. DiNatale; A. Ellis; K. Crowe-White (Journal of the Academy of Nutrition and Dietetics, 2024)

Low Mo mobility during the laterization of ultramafic bedrock: Evidence from the East Sulawesi Ophiolite, Indonesia - Adrianus Damanik; Martin Wille; Qasid Ahmad; Sukalpa Chatterjee; Sean A. Crowe; Kohen W. Bauer; Martin Grosjean; Sri Yudawati Cahyarini; Satria Bijaksana; James M. Russell; Hendrik Vogel (Chemical Geology, 2024)

Investigating leatherback surface behavior using a novel tag design and machine learning - Rick Rogers; Kate H. Choate; Leah M. Crowe; Joshua M. Hatch; Michael C. James; Eric Matzen; Samir H. Patel; Christopher R. Sasso; Liese A. Siemann; Heather L. Haas (Journal of Experimental Marine Biology and Ecology, 2024)

Controlling Cronobacter spp. in dairy manufacturing – Fundamental characteristics and practical guidance - Denise Lindsay; Jeffrey M. Farber; Ben Bright; Owen Shrubb; Donna Crowe; Tanya Soboleva (Food Control, 2024)

Marine turtles as bio-indicators of plastic pollution in the eastern Mediterranean - Emily M. Duncan; Hasan Deniz Akbora; Patrizia Baldi; Damla Beton; Annette C. Broderick; Burak Ali Cicek; Charlotte Crowe-Harland; Sophie Davey; Tess DeSerisy; Wayne J. Fuller; Julia C. Haywood; Yu Jou Hsieh; et al. (Marine Pollution Bulletin, 2024)

Complexity-functioning relationships differ across different environmental conditions - Mariana Mayer-Pinto; Amelia Caley; Antony M. Knights; Laura Airoldi; Melanie J. Bishop; Paul Brooks; Ricardo Coutinho; Tasman Crowe; Paolo Mancuso; Lais P.D. Naval-Xavier; Louise B. Firth; Rafael Menezes; et al. (Journal of Environmental Management, 2024)

Shape and Size Variation in Elapid Snake Fangs and the Effects of Phylogeny and Diet - Alessandro Palci; Michael S. Y. Lee; Jenna M. Crowe-Riddell; Emma Sherratt (Evolutionary Biology, 2023)
Recent studies have found correlations between the shape of snake teeth/fangs and diet. These studies were done at a very broad phylogenetic scale, making it desirable to test if correlations are still detectable at a narrower evolutionary scale, specifically within the family Elapidae. To this end, we studied fang shape in a dense selection of elapids representing most genera worldwide (74%). We used three-dimensional geometric morphometrics to analyse fang diversity and evaluate possible correlations between fang shape, fang size, and diet. We detected weak phylogenetic signal for both shape and absolute fang size, and found that evolutionary allometry contributes a small proportion of the among-species variation. The distribution of elapid fangs in morphospace was found to be surprisingly conservative, with only a few outliers. The only three dietary categories that were found to have a significant effect on fang shape are mammals, lizards, and reptile eggs, with mammals having a significant effect also on absolute but not relative fang size. Our results show that there are disparate patterns in fang-diet relationships at different evolutionary scales. Across all venomous snakes, previous work found that fangs are strongly influenced by diet, but within elapids our study shows these same associations are weaker and often non-significant. This could result from limitations in these types of studies, or could reflect the fact that elapids are a relatively young clade, where recent extensive divergences in diet have yet to be mirrored in fang shape, suggesting a lag between changes in ecology and dental morphology.

Application of Umami Tastants for Sodium Reduction in Food: An Evidence Analysis Center Scoping Review - Kristi M. Crowe-White; Megan Baumler; Erica Gradwell; Vijaya Juturu; Dana Angelo White; Deepa Handu (Journal of the Academy of Nutrition and Dietetics, 2023)

A global assessment of forest integrity within Key Biodiversity Areas - Olivia Crowe; Alison E. Beresford; Graeme M. Buchanan; Hedley S. Grantham; Ashley T. Simkins; James E.M. Watson; Stuart H.M. Butchart (Biological Conservation, 2023)

Online updating of obstacle positions when intercepting a virtual target - Emily M. Crowe; Jeroen B. J. Smeets; Eli Brenner (Experimental Brain Research, 2023)
People rely upon sensory information in the environment to guide their actions. Ongoing goal-directed arm movements are constantly adjusted to the latest estimate of both the target and hand’s positions. Does the continuous guidance of ongoing arm movements also consider the latest visual information of the position of obstacles in the surrounding? To find out, we asked participants to slide their finger across a screen to intercept a laterally moving virtual target while moving through a gap that was created by two virtual circular obstacles. At a fixed time during each trial, the target suddenly jumped slightly laterally while still continuing to move. In half the trials, the size of the gap changed at the same moment as the target jumped. As expected, participants adjusted their movements in response to the target jump. Importantly, the magnitude of this response depended on the new size of the gap. If participants were told that the circles were irrelevant, changing the gap between them had no effect on the responses. This shows that obstacles’ instantaneous positions can be considered when visually guiding goal-directed movements.

Water motion as a conditioning mechanism to improve the yield of the sugar kelp Saccharina latissima (Phaeophyceae) - Louise Kregting; Emma Healey; Molly Crowe; Eoghan M. Cunningham (Algal Research, 2023)

A global assessment of the prevalence of current and potential future infrastructure in Key Biodiversity Areas - Ashley T. Simkins; Alison E. Beresford; Graeme M. Buchanan; Olivia Crowe; Wendy Elliott; Pablo Izquierdo; David J. Patterson; Stuart H.M. Butchart (Biological Conservation, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

How similar are responses to background motion and target displacements? - Emily M. Crowe; Patou Vellekoop; Chermaine van Meteren; Jeroen B. J. Smeets; Eli Brenner (Experimental Brain Research, 2022)
When making a goal-directed movement towards a target, our hand follows abrupt background motion. This response resembles that of a shift in the target’s position. Does background motion simply change the position towards which the movement is guided? If so, the response to background motion should resemble the response to a target displacement. To find out whether this is the case, we ran two exploratory studies where we asked participants to hit a moving target at a specified moment. At various times during the hand’s movement, the background could move briefly at one of several speeds, and for various durations. The response to abrupt background motion was larger when the background moved later in the movement and when the background moved faster, in line with known responses to target displacements. The response to a second epoch of background motion was smaller than it would have been if there had been no first epoch, in contrast to responses to multiple target displacements. If the background was already moving before the target appeared, the hand even moved in the opposite direction. Thus, the response to background motion and that to a target displacement are clearly not identical, but they do share several features.

Assessing discards in an illegal small-scale fishery using fisher-led reporting - T. Mendo; J. Mendo; J. M. Ransijn; I. Gomez; P. Gil-Kodaka; J. Fernández; R. Delgado; A. Travezaño; R. Arroyo; K. Loza; P. McCann; S. Crowe; et al. (Reviews in Fish Biology and Fisheries, 2022)
About a third of all marine fish in the world are caught in Small-Scale Fisheries (SSF). SSF are increasingly recognised as essential for food security and livelihoods for vulnerable and economically fragile communities globally. Although individual SSF vessels are usually perceived as having little impact on the ecosystem, the cumulative impact of gear type and number of vessels may be substantial. Bottom trawling is a common fishing method that can greatly influence the marine ecosystem by damaging the seafloor and generating high levels of discards. However, appropriate sampling coverage using on-board observer programmes to collect these data from SSF are rare, as they are expensive and pose logistical constraints. A mobile App was used to assess whether self-reporting by fishers could provide reliable fine-scale information on fishing effort and discards over time in an illegal shrimp trawling fishery in northern Peru. Maps depicting the spatial distribution of trawling effort and the proportion of discards from observers and fishers were compared using the Similarity in Means (SIM) Index, which ranges from 0 when spatial patterns differ completely to 1 when spatial patterns are very similar. High levels of agreement between spatio-temporal patterns of effort (SIM Index = 0.81) and discards (0.96) were found between fisher and observer maps. Moreover, far greater spatial coverage was accomplished by fishers, suggesting that self-reporting via an App represents a useful approach to collect reliable fisheries data as an initial step for effective monitoring and management of these fisheries.

Phanerozoic history of the Pilbara region: implications for iron mineralisation - C. S. Perring; J. M. A. Hronsky; M. Crowe (Australian Journal of Earth Sciences, 2022)

Maternal Lineage and Habitat Use Patterns Explain Variation in the Fecundity of a Critically Endangered Baleen Whale - Ana L. Bishop; Leah M. Crowe; Philip K. Hamilton; Erin L. Meyer-Gutbrod (Frontiers in Marine Science, 2022)
The critically endangered North Atlantic right whale population ( Eubalaena glacialis ) has experienced multiple periods of decreased reproduction within its observable history, which have played a role in the overall decline of the species. In addition to this synchronized variation in reproduction across the population, there exists considerable individual variation in fecundity. To determine the impacts of family history and habitat use behavior on these individual variations in fecundity, photo identification data collected during four decades of visual monitoring were used to create a calving index for sexually mature females that could be used to evaluate matrilineal influence on fecundity. Reproductive life histories were analyzed to assess fecundity variation within matrilines over time. Individual variations in fecundity were also assessed with respect to a recent climate-driven habitat distribution shift by a loyal cohort of right whales that use the Gulf of St. Lawrence during the summer and autumn seasons. Lifetime fecundity in the oldest known living reproductive female, or matriarch, in a matriline was positively associated with the fecundity of her female progeny. Sexually mature females that have used the Gulf of St. Lawrence since 2015 were significantly more likely to give birth over this time period compared to individuals who did not use that habitat. Individuals of both sexes were significantly more likely to use the Gulf of St. Lawrence if their mothers did as well; however, this association declined as offspring aged. These results provide insight on the environmental, behavioral, and genetic factors that contribute to individual variation in fecundity. Low calving rates and increased dangers posed by habitat use shifts in the past decade have played a major role in the species’ decline, and these new insights into the mechanistic drivers of right whale reproduction and habitat use show that lineage guides progeny behavior and reproductive success. As anthropogenic climate change continues to disrupt right whale seasonal distributions through changing ocean circulation patterns, understanding the demographic consequences of novel habitat use patterns will be essential to updating protective policies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The influences of target size and recent experience on the vigour of adjustments to ongoing movements - Eli Brenner; Hidde Hardon; Ryan Moesman; Emily M. Crowe; Jeroen B. J. Smeets (Experimental Brain Research, 2022)
People adjust their on-going movements to changes in the environment. It takes about 100 ms to respond to an abrupt change in a target’s position. Does the vigour of such responses depend on the extent to which responding is beneficial? We asked participants to tap on targets that jumped laterally once their finger started to move. In separate blocks of trials the target either remained at the new position so that it was beneficial to respond to the jump, or jumped back almost immediately so that it was disadvantageous to do so. We also varied the target’s size, because a smaller, less vigorous adjustment is enough to place the finger within a larger target. There was a systematic relationship between the vigour of the response and the remaining time until the tap: the shorter the remaining time the more vigorous the response. This relationship did not depend on the target’s size or whether or not the target jumped back. It was already known that the vigour of responses to target jumps depends on the magnitude of the jump and on the time available for adjusting the movement to that jump. We show that the vigour of the response is precisely tuned to the time available for making the required adjustment irrespective of whether responding in this manner is beneficial.

The use of environmental DNA metabarcoding and quantitative PCR for molecular detection of marine invasive non-native species associated with artificial structures - Laura M. Gargan; Paul R. Brooks; Siobhan R. Vye; Joseph E. Ironside; Stuart R. Jenkins; Tasman P. Crowe; Jens Carlsson (Biological Invasions, 2022)

Origin and expansion of the world’s most widespread pinniped: Range‐wide population genomics of the harbour seal ( Phoca vitulina ) - Xiaodong Liu; Suzanne Rønhøj Schjøtt; Sandra M. Granquist; Aqqalu Rosing‐Asvid; Rune Dietz; Jonas Teilmann; Anders Galatius; Kristina Cammen; Greg O’Corry‐Crowe; Karin Harding; Tero Härkönen; Ailsa Hall; et al. (Molecular Ecology, 2022)
The harbour seal ( Phoca vitulina ) is the most widely distributed pinniped, occupying a wide variety of habitats and climatic zones across the Northern Hemisphere. Intriguingly, the harbour seal is also one of the most philopatric seals, raising questions as to how it colonized its current range. To shed light on the origin, remarkable range expansion, population structure and genetic diversity of this species, we used genotyping‐by‐sequencing to analyse ~13,500 biallelic single nucleotide polymorphisms from 286 individuals sampled from 22 localities across the species’ range. Our results point to a Northeast Pacific origin of the harbour seal, colonization of the North Atlantic via the Canadian Arctic, and subsequent stepping‐stone range expansions across the North Atlantic from North America to Europe, accompanied by a successive loss of genetic diversity. Our analyses further revealed a deep divergence between modern North Pacific and North Atlantic harbour seals, with finer‐scale genetic structure at regional and local scales consistent with strong philopatry. The study provides new insights into the harbour seal's remarkable ability to colonize and adapt to a wide range of habitats. Furthermore, it has implications for current harbour seal subspecies delineations and highlights the need for international and national red lists and management plans to ensure the protection of genetically and demographically isolated populations.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Educating the Next Generation of Undergraduate URM Cancer Scientists: Results and Lessons Learned from a Cancer Research Partnership Scholar Program - Elinor Gaida; Anthony J. Barrios; Roland Wolkowicz; Sheila E. Crowe; Sanford I. Bernstein; Mercedes A. Quintana Serrano; Jill N. Dumbauld; Bilge Pakiz; Richard M. Cripps; Elva M. Arredondo; Maria Elena Martinez; Hala Madanat (Journal of Cancer Education, 2021)

Turbulence in a small boreal lake: Consequences for air–water gas exchange - Sally MacIntyre; David Bastviken; Lars Arneborg; Adam T. Crowe; Jan Karlsson; Andreas Andersson; Magnus Gålfalk; Anna Rutgersson; Eva Podgrajsek; John M. Melack (Limnology and Oceanography, 2021)
The hydrodynamics within small boreal lakes have rarely been studied, yet knowing whether turbulence at the air–water interface and in the water column scales with metrics developed elsewhere is essential for computing metabolism and fluxes of climate‐forcing trace gases. We instrumented a humic, 4.7 ha, boreal lake with two meteorological stations, three thermistor arrays, an infrared (IR) camera to quantify surface divergence, obtained turbulence as dissipation rate of turbulent kinetic energy ( ε ) using an acoustic Doppler velocimeter and a temperature‐gradient microstructure profiler, and conducted chamber measurements for short periods to obtain fluxes and gas transfer velocities ( k ). Near‐surface ε varied from 10 −8 to 10 −6 m 2 s −3 for the 0–4 m s −1 winds and followed predictions from Monin–Obukhov similarity theory. The coefficient of eddy diffusivity in the mixed layer was up to 10 −3 m 2 s −1 on the windiest afternoons, an order of magnitude less other afternoons, and near molecular at deeper depths. The upper thermocline upwelled when Lake numbers ( L N ) dropped below four facilitating vertical and horizontal exchange. k computed from a surface renewal model using ε agreed with values from chambers and surface divergence and increased linearly with wind speed. Diurnal thermoclines formed on sunny days when winds were −1 , a condition that can lead to elevated near‐surface ε and k . Results extend scaling approaches developed in the laboratory and for larger water bodies, illustrate turbulence and k are greater than expected in small wind‐sheltered lakes, and provide new equations to quantify fluxes.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Influence of mouth rinse use on the enterosalivary pathway and blood pressure regulation: A systematic review - Katelyn E. Senkus; Kristi M. Crowe-White (Critical Reviews in Food Science and Nutrition, 2020)

Fruits, vegetables, and health: A comprehensive narrative, umbrella review of the science and recommendations for enhanced public policy to improve intake - Taylor C. Wallace; Regan L. Bailey; Jeffrey B. Blumberg; Britt Burton-Freeman; C-y. Oliver Chen; Kristi M. Crowe-White; Adam Drewnowski; Shirin Hooshmand; Elizabeth Johnson; Richard Lewis; Robert Murray; Sue A. Shapses; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Quasi-simultaneous 3D printing of muscle-, lung- and bone-equivalent media: a proof-of-concept study - T. Kairn; M. Zahrani; N. Cassim; A. G. Livingstone; P. H. Charles; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2020)

Examining the roles of working memory and visual attention in multiple object tracking expertise - David J. Harris; Mark R. Wilson; Emily M. Crowe; Samuel J. Vine (Cognitive Processing, 2020)
When tracking multiple moving targets among visually similar distractors, human observers are capable of distributing attention over several spatial locations. It is unclear, however, whether capacity limitations or perceptual–cognitive abilities are responsible for the development of expertise in multiple object tracking. Across two experiments, we examined the role of working memory and visual attention in tracking expertise. In Experiment 1, individuals who regularly engaged in object tracking sports (soccer and rugby) displayed improved tracking performance, relative to non-tracking sports (swimming, rowing, running) ( p = 0.02, η p 2 = 0.163), but no differences in gaze strategy ( ps > 0.31). In Experiment 2, participants trained on an adaptive object tracking task showed improved tracking performance ( p = 0.005, d = 0.817), but no changes in gaze strategy ( ps > 0.07). They did, however, show significant improvement in a working memory transfer task ( p < 0.001, d = 0.970). These findings indicate that the development of tracking expertise is more closely linked to processing capacity limits than perceptual–cognitive strategies.

Phototactic tails: Evolution and molecular basis of a novel sensory trait in sea snakes - Jenna M. Crowe‐Riddell; Bruno F. Simões; Julian C. Partridge; David M. Hunt; Steven Delean; Julian G. Schwerdt; James Breen; Alastair Ludington; David J. Gower; Kate L. Sanders (Molecular Ecology, 2019)
Dermal phototaxis has been reported in a few aquatic vertebrate lineages spanning fish, amphibians and reptiles. These taxa respond to light on the skin of their elongate hind‐bodies and tails by withdrawing under cover to avoid detection by predators. Here, we investigated tail phototaxis in sea snakes (Hydrophiinae), the only reptiles reported to exhibit this sensory behaviour. We conducted behavioural tests in 17 wild‐caught sea snakes of eight species by illuminating the dorsal surface of the tail and midbody skin using cold white, violet, blue, green and red light. Our results confirmed phototactic tail withdrawal in the previously studied Aipysurus laevis , revealed this trait for the first time in A. duboisii and A. tenuis , and suggested that tail photoreceptors have peak spectral sensitivities between blue and green light (457–514 nm). Based on these results, and an absence of photoresponses in five Aipysurus and Hydrophis species, we tentatively infer that tail phototaxis evolved in the ancestor of a clade of six Aipysurus species (comprising 10% of all sea snakes). Quantifying tail damage, we found that the probability of sustaining tail injuries was not influenced by tail phototactic ability in snakes. Gene profiling showed that transcriptomes of both tail skin and body skin lacked visual opsins but contained melanopsin ( opn4x ) in addition to key genes of the retinal regeneration and phototransduction cascades. This work suggests that a nonvisual photoreceptor (e.g., Gq rhabdomeric) signalling pathway underlies tail phototaxis, and provides candidate gene targets for future studies of this unusual sensory innovation in reptiles.

Future Directions in the Research and Management of Marine Snakes - Vinay Udyawer; Peter Barnes; Xavier Bonnet; François Brischoux; Jenna M. Crowe-Riddell; Blanche D’Anastasi; Bryan G. Fry; Amber Gillett; Claire Goiran; Michael L. Guinea; Harold Heatwole; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)

Characterization of large basking shark Cetorhinus maximus aggregations in the western North Atlantic Ocean - L. M. Crowe; O. O'Brien; T. H. Curtis; S. M. Leiter; R. D. Kenney; P. Duley; S. D. Kraus (Journal of Fish Biology, 2018)
Cetorhinus maximus aggregations recorded during extensive aerial survey efforts off the north‐eastern United States between 1980 and 2013 included aggregations centring on sightings with group sizes of at least 30 individuals. These aggregations occurred in summer and autumn months and included aggregation sizes of up to 1398 individuals, the largest aggregation ever reported for this species. The aggregations were associated with sea surface temperatures of 13–24° C and chlorophyll‐a concentrations of 0·4–2·6 mg m −3 and during one aggregation, a high abundance of zooplankton prey was present. Photogrammetric tools allowed for the estimation of total body lengths ranging between 4 and 8 m. Characterization of these events provides new insight into the potential biological function of large aggregations in this species.

Diverse effects of invasive ecosystem engineers on marine biodiversity and ecosystem functions: A global review and meta‐analysis - Tamar Guy‐Haim; Devin A. Lyons; Jonne Kotta; Henn Ojaveer; Ana M. Queirós; Eva Chatzinikolaou; Christos Arvanitidis; Serena Como; Paolo Magni; Andrew J. Blight; Helen Orav‐Kotta; Paul J. Somerfield; et al. (Global Change Biology, 2018)
Invasive ecosystem engineers ( IEE ) are potentially one of the most influential types of biological invaders. They are expected to have extensive ecological impacts by altering the physical–chemical structure of ecosystems, thereby changing the rules of existence for a broad range of resident biota. To test the generality of this expectation, we used a global systematic review and meta‐analysis to examine IEE effects on the abundance of individual species and communities, biodiversity (using several indices) and ecosystem functions, focusing on marine and estuarine environments. We found that IEE had a significant effect (positive and negative) in most studies testing impacts on individual species, but the overall (cumulative) effect size was small and negative. Many individual studies showed strong IEE effects on community abundance and diversity, but the direction of effects was variable, leading to statistically non‐significant overall effects in most categories. In contrast, there was a strong overall effect on most ecosystem functions we examined. IEE negatively affected metabolic functions and primary production, but positively affected nutrient flux, sedimentation and decomposition. We use the results to develop a conceptual model by highlighting pathways whereby IEE impact communities and ecosystem functions, and identify several sources of research bias in the IEE ‐related invasion literature. Only a few of the studies simultaneously quantified IEE effects on community/diversity and ecosystem functions. Therefore, understanding how IEE may alter biodiversity–ecosystem function relationships should be a primary focus of future studies of invasion biology. Moreover, the clear effects of IEE on ecosystem functions detected in our study suggest that scientists and environmental managers ought to examine how the effects of IEE might be manifested in the services that marine ecosystems provide to humans.

Short‐term survival of Steller sea lion ( Eumetopias jubatus ) pups: Investigating the effect of health status on survival - Grey W. Pendleton; Kelly K. Hastings; Lorrie D. Rea; Lauri A. Jemison; Greg M. O'Corry‐Crowe; Kimberlee B. Beckmen (Marine Mammal Science, 2016)
We estimated survival probabilities for Steller sea lion ( Eumetopias jubatus ) pups from 3 wk to 6 wk old and from 6 wk to 1 yr at three rookeries in southeastern Alaska. We also investigated the effect of mass, body condition, health variables, and the genetic origin on 3–6 wk survival. Survival differed substantially among rookeries and between sexes, with survival lowest at Hazy Islands, intermediate at White Sisters, and highest at Graves Rocks and survival lower for males than females. Body mass, body condition, and hematocrit were positively related to survival and blood %H 2 O and haptoglobin level (for females; no relationship for males) were negatively related to survival. Taking predictor variables collectively, sea lion pups at Hazy Islands, which had the lowest survival probability, had the lowest mass, hematocrit, and hemoglobin, and had high levels of blood %H 2 O, and hookworm infection. Values from Graves Rocks, which had the highest survival, were the opposite of those from Hazy Island ( e.g ., high mass, body condition, hematocrit, and hemoglobin), while those from White Sisters (intermediate survival) had varying means ( e.g ., high hematocrit and hemoglobin and low hookworms, but also low body condition); these patterns suggest that physiological factors potentially underlie rookery differences in survival.

Velocity measurements in inclined negatively buoyant jets - A. T. Crowe; M. J. Davidson; R. I. Nokes (Environmental Fluid Mechanics, 2016)

The microRNA-29 family in cartilage homeostasis and osteoarthritis - Linh T. T. Le; Tracey E. Swingler; Natalie Crowe; Tonia L. Vincent; Matthew J. Barter; Simon T. Donell; Anne M. Delany; Tamas Dalmay; David A. Young; Ian M. Clark (Journal of Molecular Medicine, 2016)

There are no whole truths in meta‐analyses: all their truths are half‐truths - Devin A. Lyons; Christos Arvanitidis; Andrew J. Blight; Eva Chatzinikolaou; Tamar Guy‐Haim; Jonne Kotta; Ana M. Queirós; Gil Rilov; Paul J. Somerfield; Tasman P. Crowe (Global Change Biology, 2016)

Microbial life in Bourlyashchy, the hottest thermal pool of Uzon Caldera, Kamchatka - Nikolay A. Chernyh; Andrey V. Mardanov; Vadim M. Gumerov; Margarita L. Miroshnichenko; Alexander V. Lebedinsky; Alexander Y. Merkel; Douglas Crowe; Nikolay V. Pimenov; Igor I. Rusanov; Nikolay V. Ravin; Mary Ann Moran; Elizaveta A. Bonch-Osmolovskaya (Extremophiles, 2015)

HIV eradication symposium: will the brain be left behind? - B. J. Brew; K. Robertson; E. J. Wright; M. Churchill; S. M. Crowe; L. A. Cysique; S. Deeks; J. V. Garcia; B. Gelman; L. R. Gray; T. Johnson; J. Joseph; et al. (Journal of NeuroVirology, 2015)

Evaluating Bioactive Food Components in Obesity and Cancer Prevention - Kristi M. Crowe; David Allison (Critical Reviews in Food Science and Nutrition, 2015)

Functional analyses of three acyl‐ CoA synthetases involved in bile acid degradation in P seudomonas putida DOC 21 - Álvaro Barrientos; Estefanía Merino; Israël Casabon; Joaquín Rodríguez; Adam M. Crowe; Johannes Holert; Bodo Philipp; Lindsay D. Eltis; Elías R. Olivera; José M. Luengo (Environmental Microbiology, 2015)
Summary P seudomonas putida DOC 21, a soil‐dwelling proteobacterium, catabolizes a variety of steroids and bile acids. Transposon mutagenesis and bioinformatics analyses identified four clusters of steroid degradation ( std ) genes encoding a single catabolic pathway. The latter includes three predicted acyl‐ CoA synthetases encoded by stdA1 , stdA2 and stdA3 respectively. The Δ stdA1 and Δ stdA2 deletion mutants were unable to assimilate cholate or other bile acids but grew well on testosterone or 4‐androstene‐3,17‐dione ( AD ). In contrast, a Δ stdA3 mutant grew poorly in media containing either testosterone or AD . When cells were grown with succinate in the presence of cholate, Δ stdA1 accumulated Δ 1/4 ‐3‐ketocholate and Δ 1,4 ‐3‐ketocholate, whereas Δ stdA2 only accumulated 7α,12α‐dihydroxy‐3‐oxopregna‐1,4‐diene‐20‐carboxylate ( DHOPDC ). When incubated with testosterone or bile acids, Δ stdA3 accumulated 3aα‐ H ‐4α(3′propanoate)‐7aβ‐methylhexahydro‐1,5‐indanedione ( HIP ) or the corresponding hydroxylated derivative. Biochemical analyses revealed that StdA1 converted cholate, 3‐ketocholate, Δ 1/4 ‐3‐ketocholate, and Δ 1,4 ‐3‐ketocholate to their CoA thioesters, while StdA 2 transformed DHOPDC to DHOPDC ‐ CoA . In contrast, purified StdA 3 catalysed the CoA thioesterification of HIP and its hydroxylated derivatives. Overall, StdA 1, StdA 2 and StdA 3 are acyl‐ CoA synthetases required for the complete degradation of bile acids: StdA 1 and StdA 2 are involved in degrading the C ‐17 acyl chain, whereas StdA 3 initiates degradation of the last two steroid rings. The study highlights differences in steroid catabolism between P roteobacteria and A ctinobacteria .

Microbes in beach sands: integrating environment, ecology and public health - Richard L. Whitman; Valerie J. Harwood; Thomas A. Edge; Meredith B. Nevers; Muruleedhara Byappanahalli; Kannappan Vijayavel; João Brandão; Michael J. Sadowsky; Elizabeth Wheeler Alm; Allan Crowe; Donna Ferguson; Zhongfu Ge; et al. (Reviews in Environmental Science and Bio/Technology, 2014)

Macroalgal blooms alter community structure and primary productivity in marine ecosystems - Devin A. Lyons; Christos Arvanitidis; Andrew J. Blight; Eva Chatzinikolaou; Tamar Guy‐Haim; Jonne Kotta; Helen Orav‐Kotta; Ana M. Queirós; Gil Rilov; Paul J. Somerfield; Tasman P. Crowe (Global Change Biology, 2014)
Eutrophication, coupled with loss of herbivory due to habitat degradation and overharvesting, has increased the frequency and severity of macroalgal blooms worldwide. Macroalgal blooms interfere with human activities in coastal areas, and sometimes necessitate costly algal removal programmes. They also have many detrimental effects on marine and estuarine ecosystems, including induction of hypoxia, release of toxic hydrogen sulphide into the sediments and atmosphere, and the loss of ecologically and economically important species. However, macroalgal blooms can also increase habitat complexity, provide organisms with food and shelter, and reduce other problems associated with eutrophication. These contrasting effects make their overall ecological impacts unclear. We conducted a systematic review and meta‐analysis to estimate the overall effects of macroalgal blooms on several key measures of ecosystem structure and functioning in marine ecosystems. We also evaluated some of the ecological and methodological factors that might explain the highly variable effects observed in different studies. Averaged across all studies, macroalgal blooms had negative effects on the abundance and species richness of marine organisms, but blooms by different algal taxa had different consequences, ranging from strong negative to strong positive effects. Blooms' effects on species richness also depended on the habitat where they occurred, with the strongest negative effects seen in sandy or muddy subtidal habitats and in the rocky intertidal. Invertebrate communities also appeared to be particularly sensitive to blooms, suffering reductions in their abundance, species richness, and diversity. The total net primary productivity, gross primary productivity, and respiration of benthic ecosystems were higher during macroalgal blooms, but blooms had negative effects on the productivity and respiration of other organisms. These results suggest that, in addition to their direct social and economic costs, macroalgal blooms have ecological effects that may alter their capacity to deliver important ecosystem services.

Monitoring white whales (Delphinapterus leucas) with echolocation loggers - Manuel Castellote; Ruth H. Leeney; Gregory O’Corry-Crowe; Rauno Lauhakangas; Kit M. Kovacs; William Lucey; Vera Krasnova; Christian Lydersen; Kathleen M. Stafford; Roman Belikov (Polar Biology, 2013)

Development and implementation of allocation arrangements for recreational and commercial fishing sectors in W estern A ustralia - F. M. Crowe; I. G. Longson; L. M. Joll (Fisheries Management and Ecology, 2013)
This paper examines why W estern A ustralia's I ntegrated F isheries M anagement ( IFM ) policy was adopted, its development, achievements, lessons learned and future directions. Adopted in 2004, IFM aims to achieve and maintain fish resource sustainability through optimal catch share arrangements between competing users. It involves setting an allowable harvest level for each resource, using an independent allocation committee process to allocate explicit catch shares for commercial, recreational and customary sectors, and monitoring sectoral catch. IFM provides guidance for managing each sector within its catch share, providing access to that share, and developing reallocation mechanisms to transfer sectoral catch shares. The three most important multi‐sector resources, western rock lobster, P anulirus cygnus G eorge, metropolitan R oe's abalone, H aliotis roei Grey, and west coast demersal scalefish, have undergone the allocation process. The first two are operational while the third is almost complete. Allocation outcomes demonstrate the need to account for each sector's catch, with credible scientific data to underpin decision‐making, independent transparent allocation processes, robust sectoral representation, workable reallocation mechanisms and management arrangements to ensure that all sectors can access their allocated share. IFM generates fair decisions for optimal resource use to reduce intersectoral conflict and provide better community outcomes, with wide applicability across other jurisdictions.

Population genetic structure and evolutionary history of North Atlantic beluga whales (Delphinapterus leucas) from West Greenland, Svalbard and the White Sea - Gregory O’Corry-Crowe; Christian Lydersen; Mads Peter Heide-Jørgensen; Lauren Hansen; Lev M. Mukhametov; Outi Dove; Kit M. Kovacs (Polar Biology, 2010)

Prospective study of physical activity and risk of primary adenocarcinomas of the oesophagus and stomach in the EPIC (European Prospective Investigation into Cancer and nutrition) cohort - José María Huerta; Carmen Navarro; María-Dolores Chirlaque; María-José Tormo; Karen Steindorf; Genevieve Buckland; Fátima Carneiro; Nina Føns Johnsen; Kim Overvad; Jakob Stegger; Anne Tjønneland; Marie-Christine Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

A magnetoencephalography study of choice bias - William M. Hedgcock; David A. Crowe; Arthur C. Leuthold; Apostolos P. Georgopoulos (Experimental Brain Research, 2010)

Regional genomic instability predisposes to complex dystrophin gene rearrangements - Junko Oshima; Daniel B. Magner; Jennifer A. Lee; Amy M. Breman; Eric S. Schmitt; Lisa D. White; Carol A. Crowe; Michelle Merrill; Parul Jayakar; Aparna Rajadhyaksha; Christine M. Eng; Daniela del Gaudio (Human Genetics, 2009)

Game theoretic model of brood parasitism in a dung beetle Onthophagus taurus - M. Crowe; M. Fitzgerald; D. L. Remington; G. D. Ruxton; J. Rychtář (Evolutionary Ecology, 2009)

Neurodegeneration and Ageing in the HAART Era - Bruce J. Brew; S. M. Crowe; A. Landay; Lucette A. Cysique; Gilles Guillemin (Journal of Neuroimmune Pharmacology, 2009)

Disturbance of intertidal soft sediment assemblages caused by swinging boat moorings - R. J. H. Herbert; T. P. Crowe; S. Bray; M. Sheader (Hydrobiologia, 2009)

Climate change causes rapid changes in the distribution and site abundance of birds in winter - ILYA M. D. MACLEAN; GRAHAM E. AUSTIN; MARK M. REHFISCH; JAN BLEW; OLIVIA CROWE; SIMON DELANY; KOEN DEVOS; BERNARD DECEUNINCK; KLAUS GÜNTHER; KARSTEN LAURSEN; MARC VAN ROOMEN; JOHANNES WAHL (Global Change Biology, 2008)
Detecting coherent signals of climate change is best achieved by conducting expansive, long‐term studies. Here, using counts of waders ( Charadrii ) collected from ca. 3500 sites over 30 years and covering a major portion of western Europe, we present the largest‐scale study to show that faunal abundance is influenced by climate in winter. We demonstrate that the ‘weighted centroids’ of populations of seven species of wader occurring in internationally important numbers have undergone substantial shifts of up to 115 km, generally in a northeasterly direction. To our knowledge, this shift is greater than that recorded in any other study, but closer to what would be expected as a result of the spatial distribution of ecological zones. We establish that year‐to‐year changes in site abundance have been positively correlated with concurrent changes in temperature, but that this relationship is most marked towards the colder extremities of the birds' range, suggesting that shifts have occurred as a result of range expansion and that responses to climate change are temperature dependent. Many attempts to model the future impacts of climate change on the distribution of organisms, assume uniform responses or shifts throughout a species' range or with temperature, but our results suggest that this may not be a valid approach. We propose that, with warming temperatures, hitherto unsuitable sites in northeastern Europe will host increasingly important wader numbers, but that this may not be matched by declines elsewhere within the study area. The need to establish that such changes are occurring is accentuated by the statutory importance of this taxon in the designation of protected areas.

Green manure effects on soil quality in relation to suppression of Verticillium wilt of potatoes - N. Ochiai; M. L. Powelson; F. J. Crowe; R. P. Dick (Biology and Fertility of Soils, 2008)

Histamine induces interleukin-6 expression in the human synovial sarcoma cell line (SW982) through the H1 receptor - S. L. Wang; S. Malany; Q. Wang; M. A. Santos; P. D. Crowe; R. A. Maki (Inflammation Research, 2006)

Diet of Pacific sleeper shark, a potential Steller sea lion predator, in the north‐east Pacific Ocean - M. F. Sigler; L. B. Hulbert; C. R. Lunsford; N. H. Thompson; K. Burek; G. O’Corry‐Crowe; A. C. Hirons (Journal of Fish Biology, 2006)
Pacific sleeper sharks Somniosus pacificus were captured near Steller sea lion Eumetopias jubatus rookeries during the period when Steller sea lion pups are most vulnerable to Pacific sleeper shark predation (first water entrance and weaning). Analysis of stomach contents revealed that teleosts were the dominant prey in August and cephalopods were the dominant prey in May ( n = 198). Marine mammals were found in 15% of stomachs regardless of season, but no Steller sea lion tissues were detected. Molecular genetic analysis identified grey whale Eschrichtius robustus and harbour seal Phoca vitulina remains in some Pacific sleeper shark stomachs. Most mammals were cetacean and at least 70% of the cetaceans were probably scavenged. Although Pacific sleeper shark and Steller sea lion ranges overlapped, so predation could potentially occur, the diet study suggested that predation on Steller sea lions is unlikely, at least when pups first enter the water or during weaning. Harbour seals were infrequent prey and may have been consumed alive. Pacific sleeper sharks consume fast‐swimming prey like Pacific salmon Oncorhynchus sp., most likely live animals rather than scavenged animals. Pacific sleeper sharks appeared to be opportunistic consumers of the available prey and carrion, feeding both on the bottom and in the water column, and their diet shifted to teleosts and cetacean carrion as the fish grew larger.

Mental maze solving: directional fMRI tuning and population coding in the superior parietal lobule - Pavlos Gourtzelidis; Charidimos Tzagarakis; Scott M. Lewis; David A. Crowe; Edward Auerbach; Trenton A. Jerde; Kâmil Uğurbil; Apostolos P. Georgopoulos (Experimental Brain Research, 2005)

New records of planktonic cyanobacteria in New Zealand freshwaters - S.A. Wood; A. L. M. Crowe; J. G. Ruck; R. G. Wear (New Zealand Journal of Botany, 2005)
New records of planktonic cyanobacteria in New Zealand freshwaters are reported. Identified for the first time were one genus, Sphaerocavum , represented by one species, and one species of Apha‐nocapsa , five species of Microcystis , and three of Anabaena. Microcystis panniformis has previously been recorded only from tropical or subtropical regions. Descriptions, drawings, and photographs of species are presented.

Structure–Activity of Valencenoid Derivatives and Their Repellence to the Formosan Subterranean Termite - Betty C. R. Zhu; Gregg Henderson; Anne M. Sauer; Ying Yu; William Crowe; Roger A. Laine (Journal of Chemical Ecology, 2003)

Dose and Enantiospecific Responses of White Pine Cone Beetles, Conophthorus coniperda, to α-Pinene in an Eastern White Pine Seed Orchard - Daniel R. Miller; Christopher M. Crowe; Christopher Asaro; Gary L. Debarr (Journal of Chemical Ecology, 2003)

Application of empirical mode decomposition to heart rate variability analysis - J. C. Echeverría; J. A. Crowe; M. S. Woolfson; B. R. Hayes-Gill (Medical & Biological Engineering & Computing, 2001)

Waterbird assemblages and associated habitat characteristics of farm ponds in the Western Cape, South Africa - Albert Froneman; Michael J. Mangnall; Robin M. Little; Timothy M. Crowe (Biodiversity and Conservation, 2001)

Middle Pleistocene interglacial deposits at Barling, Essex, England: evidence for a longer chronology for the Thames terrace sequence - D. R. Bridgland; R. C. Preece; H. M. Roe; R. M. Tipping; G. R. Coope; M. H. Field; J. E. Robinson; D. C. Schreve; K. Crowe (Journal of Quaternary Science, 2001)
Results are presented from a multidisciplinary study of fossiliferous interglacial deposits on the northern side of the Thames estuary. These fill a channel cut into London Clay bedrock and overlain by the Barling Gravel, a Thames–Medway deposit equivalent to the Lynch Hill and Corbets Tey Gravels of the Middle and Lower Thames, respectively. The channel sediments yielded diverse molluscan and ostracod assemblages, both implying fully interglacial conditions and a slight brackish influence. Pollen analysis has shown that the deposits accumulated during the early part of an interglacial. Plant macrofossils, particularly the abundance of Trapa natans , reinforce the interglacial character of the palaeontological evidence. A beetle fauna, which includes four taxa unknown in Britain at present, has allowed quantification of palaeotemperature using the mutual climatic range method ( T max 17 to 26 °C; T min −11 to 13 °C). A few vertebrate remains have been recovered from the interglacial deposits, but a much larger fauna, as well as Palaeolithic artefacts, is known from the overlying Barling Gravel. The age of the interglacial deposits is inferential. The geological context suggests a late Middle Pleistocene interglacial, part of the post‐diversion Thames system and therefore clearly post‐Anglian. This conclusion is supported by amino acid ratios from the shells of freshwater molluscs. The correlation of the overlying Barling Gravel with the Lynch Hill/Corbets Tey aggradation of the Thames valley constrains the age of the Barling interglacial to marine oxygen isotope stages 11 or 9. The presence of Corbicula fluminalis and Pisidium clessini confirms a pre‐Ipswichian (marine oxygen isotope substage 5e) age and their occurrence in the early part of the interglacial cycle at Barling precludes correlation with marine oxygen isotope stage 11, as these taxa occur only later in that interglacial at sites such as Swanscombe and Clacton. Thus by process of elimination a marine oxygen isotope stage 9 age would appear probable. Copyright © 2001 John Wiley & Sons, Ltd.

Workshop on Indices and Indicators for Climate Extremes, Asheville, NC, USA, 3–6 June 1997 Breakout Group C: Temperature Indices for Climate Extremes - C.K. Folland; C. Miller; D. Bader; M. Crowe; P. Jones; N. Plummer; M. Richman; D.E. Parker; J. Rogers; P. Scholefield (Climatic Change, 1999)

Interpreting biogeographical boundaries among Afrotropical birds: spatial patterns in richness gradients and species replacement - Paul H. Williams; Helen M. de Klerk; Timothy M. Crowe (Journal of Biogeography, 1999)
Summary Aim We analyse the geographical distribution of 1911 Afrotropical bird species using indices of three simple biogeographic patterns. The first index, the frequency of species with range edges ( T e ), is formulated to map directly the density of species distribution limits, for comparison with the results of traditional biogeographical classification and ordination procedures, in order to show variations in the strength and breadth of transition zones. The other two indices are formulated to seek to distinguish as directly as possible between two components within these transition‐zone patterns: contributions from gradients in species richness ( T g ); and contributions from replacements among species ( T r ). We test the ability of these indices to discover the same boundaries among Afrotropical bird faunas as one popular procedure for classifying areas (TWINSPAN) and then use them to look for geographical trends in the different kinds of transition zones. Location The analysis is restricted to the sub‐Saharan or Afrotropical region, excluding the Arabian Peninsula, Madagascar and all offshore islands. Methods We record the presence of each species in 1961 1°×1° grid cells of the map. To apply the three indices, each (core) grid cell in turn is compared with its neighbouring eight cells in the grid. The range edges index ( T e ) counts the number of species with range edges between the core cell and the surrounding cells. The richness gradients index ( T g ) counts the largest difference in species richness measured diametrically across the core cell in any direction when there is a consistent trend in richness along this line of three cells. The species replacements index ( T r ) counts the number of species pairs recorded within a nine‐cell neighbourhood that are not corecorded within any of the cells. Values for each of the 1961 grid cells are calculated and used to produce colour‐scale maps of transition zones. Results Large‐scale spatial patterns of variation in density of range edges ( T e ) are consistent with classifications of the same data and with most previous biogeographical classifications proposed for the region. Variation in richness gradients ( T g ) and species replacements ( T r ) explain different parts of this pattern, with transition zones around humid forests in the equatorial region being dominated by species replacement, and transition zones around deserts (most extensive in the north and south) being dominated by richness gradients. Main conclusions The three indices distinguish the spatial arrangement and intensity of different kinds of transition zones, thereby providing a first step towards a more rigorous mechanistic understanding of the different processes by which they may have arisen and are maintained. As an example of one such pattern shown by our analyses of Afrotropical birds, there is evidence for a broad latitudinal trend in the nature of transition zones in faunal composition (following the latitudinal distribution of the different kinds of habitat transitions), from being dominated by species replacements near the equator to being dominated by richness gradients further from the equator.

Letters - Timothy D. Male; Reed F. Noss; Timothy M. Crowe; Jon Paul Rodriguez; Gary K. Meffe (Conservation Biology, 1998)

Letters - Timothy D. Male; Reed F. Noss; Timothy M. Crowe; Jon Paul Rodríguez; Gary K. Meffe (Conservation Biology, 1998)

Bacteraemia in the Adult Intensive Care Unit of a Teaching Hospital in Nottingham, UK, 1985-1996 - M. Crowe; P. Ispahani; H. Humphreys; T. Kelley; R. Winter (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Surveillance of an Adult Intensive Care Unit for Long-Term Persistence of a Multi-Resistant Strain of Acinetobacter baumannii - C. A. Webster; M. Crowe; H. Humphreys; K. J. Towner (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Bacteraemia in the adult intensive care unit of a teaching hospital in Nottingham, UK, 1985–1996 - M. Crowe; P. Ispahani; H. Humphreys; T. Kelley; R. Winter (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Surveillance of an adult intensive care unit for long-term persistence of a multi-resistant strain ofAcinetobacter baumannii - C. A. Webster; M. Crowe; H. Humphreys; K. J. Towner (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Effects of Leaf Age on Oviposition and on Offspring Fitness in the Imported Willow Leaf Beetle Plagiodera versicolora (Coleoptera: Chrysomelidae) - B. H. King; M. L. Crowe; M. D. Blackmore (Journal of Insect Behavior, 1998)

DRIED DOLPHIN BLOOD ON FISHERY OBSERVER RECORDS PROVIDES DNA FOR GENETIC ANALYSES - L. S. Eggert; C. A. Lux; G. M. O'corry‐Crowe; A. E. Dizon (Marine Mammal Science, 1998)

Phylogeography, population structure and dispersal patterns of the beluga whale Delphinapterus leucas in the western Nearctic revealed by mitochondrial DNA - G. M. O'Corry‐Crowe; R. S. Suydam; A. Rosenberg; K. J. Frost; A. E. Dizon (Molecular Ecology, 1997)
The recent evolutionary history, population structure and movement patterns of beluga whales in the western Nearctic were inferred from an analysis of mitochondrial DNA control region sequence variation of 324 whales from 32 locations representing five summer concentration areas in Alaska and north‐west Canada. Phylogenetic relationships among haplotypes were inferred from parsimonious networks, and genetic subdivision was examined using haplotypic frequency‐based indices and an analysis of variance method modified for use with interhaplotypic distance data. MtDNA relationships were characterized by a series of star‐like phylogenies which, when viewed in conjunction with information on haplotype frequency and distribution, suggested a rapid radiation of beluga whales into the western Nearctic following the Pleistocene, and an early divergence of the Beaufort Sea from the Chukchi and Bering Seas subpopulations. Overall nucleotide diversity was low (0.51%) yet all major summering concentrations were significantly differentiated (Φ ST = 0.33) from one another. Stratification of samples by gender and age from the three northernmost subpopulations suggested that female cohorts from neighbouring subpopulations were more differentiated than males. Further stratification of adult animals by age revealed that older adults were substantially less subdivided among locations than younger adults, particularly for males, suggesting that dispersal, although limited, is biased toward older adult males. Overall, the patterns of mtDNA variation in beluga whales indicated that the summering concentrations are demographically, if not phyletically distinct. Population structure appears to be maintained primarily by natal homing behaviour, while asymmetries in dispersal may be associated with the type of mating system.

Extracellular polysaccharide of Nostoc commune (Cyanobacteria) inhibits fusion of membrane vesicles during desiccation - Donna R. Hill; Thomas W. Keenan; Richard F. Helm; Malcolm Potts; Lois M. Crowe; John H. Crowe (Journal of Applied Phycology, 1997)

Detection of fetal electrocardiogram signals using matched filters with adaptive normalisation - N. M. Gibson; M. S. Woolfson; J. A. Crowe (Medical & Biological Engineering & Computing, 1997)

Using patterns of distribution and diversity of Kenyan birds to select and prioritize areas for conservation - John N. Muriuki; Helen M. De Klerk; Paul H. Williams; Leon A. Bennun; Timothy M. Crowe; Edward Vanden Berge (Biodiversity and Conservation, 1997)

Does hunting affect the demography and genetic structure of the greywing francolin Francolinus africanus? - Robin M. Little; Timothy M. Crowe; W. Stewart Grant (Biodiversity and Conservation, 1993)

A clonal analysis of Neisseria meningitidis serogroup A - B. A. Crowe; T. Olyhoek; B. Neumann; B. Wall; M. Hassan-King; B. Greenwood; M. Achtman (Antonie van Leeuwenhoek, 1987)

Evidence for clonal structure inNeisseria meningitidis: Relevance to epidemiology - T. Olyhoek; B. Crowe; M. Achtman (Antonie van Leeuwenhoek, 1986)

The effects of ? motor stimulation on the interpretation of signals from muscle spindles - A. Crowe; M. Naeije; R. H. J. Tanke (Biological Cybernetics, 1982)

A method for the interpretation of signals in afferent nerves from muscle spindles - A. Crowe; M. Naeije; R. H. J. Tanke (Biological Cybernetics, 1980)

Model for the ? motor stimulation in chelonian muscle spindles - M. Naeije; A. Crowe (Biological Cybernetics, 1977)

Model of the firing frequency of the chelonian muscle spindle - M. Naeije; A. Crowe; H. de Klerk (Biological Cybernetics, 1976)